2019
DOI: 10.3856/vol47-issue4-fulltext-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary intake of phenolic compounds from mango peel extract on growth, lipid peroxidation and antioxidant enzyme activities in zebrafish (Danio rerio)

Abstract: Four experimental diets were formulated with 50, 100, 150 and 200 mg of phenolic compounds (PCs) kg-1 feed, derived from mango peel. The control diet did not contain PCs. A total of 120 male zebrafish (Danio rerio) (average weight: 166 mg) were fed for eight weeks to assess the ability of PCs to prevent lipid peroxidation and enhance antioxidant status. Growth performance was calculated at the end of the experimental trial. Lipid peroxidations in muscle and antioxidant enzyme activity in the liver were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…•and H 2 O 2 triggers oxidative stress, decreasing cellular antioxidant defenses [14], which causes oxidative liver cell damage because the liver is the main metabolizing and detoxifying organ [12]. Previous studies have reported that hypoxia-induced oxidative stress inhibits the first-line antioxidant defense, made up of CAT, SOD, and GPx in the liver of freshwater fish [9,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…•and H 2 O 2 triggers oxidative stress, decreasing cellular antioxidant defenses [14], which causes oxidative liver cell damage because the liver is the main metabolizing and detoxifying organ [12]. Previous studies have reported that hypoxia-induced oxidative stress inhibits the first-line antioxidant defense, made up of CAT, SOD, and GPx in the liver of freshwater fish [9,14].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, research has focused on finding low-cost natural antioxidants that reduce or prevent cell damage caused by hypoxia-induced oxidative stress. Plant wastes are a rich source of phenolic compounds (PCs) widely used as antioxidant additives in aquafeeds to enhance the hepatic antioxidant response and prevent its oxidative damage in fish [6,12,13]. PCs exert their antioxidant effect through the electrons/protons donation that neutralizes ROS or modulates the SOD, CAT, and GPx activities [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This assay was performed according to Lizárraga-Velázquez et al [58] and Solé et al [59] with slight modifications. Briefly, 50 µL of the supernatant were mixed with 163 µL of 1 methyl-2-phenylindole (10.3 mM, in methanol:acetonitrile, 1:3; v/v), 50 µL of distilled water and 75 µL of HCl at 37%.…”
Section: Assay For Lipid Peroxidationmentioning
confidence: 99%
“…For instance, phenolic compounds from avocado seed and peel have been demonstrated to possess antioxidant properties by showing high radical scavenging activity against ROS, such as peroxyl superoxide (ROO) (2.2-10.6 µmol TE/g) and hypochlorous acid (HOCl) (EC 50 = 5.2-8.6 µg/mL) [173]. Furthermore, phenolic compounds from mango peels, such as gallic acid and quercetin, increase the activity of CAT and reduce the MDA levels, as a biomarker of lipid peroxidation, in an in-vivo model of zebrafish (Danio rerio) [174]. Lycopene (4.9%), a tetraterpene, from tomato peel, has been demonstrated to exert antioxidant activity via reducing the levels of ROS and diminishing the DNA fragmentation induced by H 2 O 2 in L6 cells (myoblasts) [175].…”
Section: Antioxidant Propertiesmentioning
confidence: 99%